2017
DOI: 10.4172/2573-0312.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Can Functional Eccentric Muscle Control Remedies Balance Ability in Children with Spastic Diplegic Cerebral Palsy

Abstract: Background: Eccentric training redresses the consequences of spastic muscle shortening by altering the lengthtension characteristics of muscle to operate at longer lengths

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous studies investigated the effects of resistance training in children with CP and reported positive influences on gait, gross motor function, muscle strength, spasticity and equilibrium [1,[13][14][15]. However, no studies to date have focused on the effects of either progressive functional strength training training or conventional physiotherapy on SVMC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the effects of resistance training in children with CP and reported positive influences on gait, gross motor function, muscle strength, spasticity and equilibrium [1,[13][14][15]. However, no studies to date have focused on the effects of either progressive functional strength training training or conventional physiotherapy on SVMC.…”
Section: Introductionmentioning
confidence: 99%